1996
DOI: 10.3109/00365529609031982
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activators and Plasminogen Activator Inhibitor in Portal Blood from Patients with and without Gastric Malignancy

Abstract: In both groups tPA: Act and scuPA: Act levels were significantly higher in portal blood than in peripheral blood, but tPA: Ag and PAI: Act levels did not differ. PAI: Act levels were significantly lower in patients with malignant disease, but levels of the other markers did not differ in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The results indicate that in the splanchnic circulation the majority of rPA is released in its free active form. This observation is supported by a recent study on patients undergoing gastric surgery, which showed that there was a significantly higher ratio of active to total t-PA in the portal as compared to brachial vein (25).In contrast, we observed no significant changes of the ratio of active to total t-PA upon passage through the coronary or pulmonary vascular bed.…”
Section: Discussionsupporting
confidence: 90%
“…The results indicate that in the splanchnic circulation the majority of rPA is released in its free active form. This observation is supported by a recent study on patients undergoing gastric surgery, which showed that there was a significantly higher ratio of active to total t-PA in the portal as compared to brachial vein (25).In contrast, we observed no significant changes of the ratio of active to total t-PA upon passage through the coronary or pulmonary vascular bed.…”
Section: Discussionsupporting
confidence: 90%